PENGARUH KUALITAS AUDIT, KOMITE AUDIT, KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Lidiawati, Novi; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test the influence of audit quality, audit committee, institutional ownership, firm size, and leverage to the earnings management which has been done by the property and real estate companies in Indonesia. The population is property and Real Estate Companies which are listed in Indonesia Stock Exchange (IDX) from 2011 to 2014 periods. The samples are 25 property and real estate companies which have been selected by using purposive sampling. The analysis method by using multiple linear regressions analysis technique. The result of this research shows that audit quality does not have any influence to the earnings management, it means that the companies do not pay attention to the Public Accounting Firm which will audit the company. The audit committee has negative influence to the earnings management, it means that audit committee in the company grow it will reduce the earnings management practice. The institutional ownership does not have any influence to the earnings management. Firm size has positive influence to the profit management, it means that large company to do the earnings management practice. Leverage does not have any influence to the earnings management it means that the company has a safe leverage.Keywords: audit quality, audit committee, firm size, leverage, earnings management